تطوير المواد التعليمية لدرس خصوصي للغة العربية 2 على أساس أندرويد قادولار لطلاب جامعة سوراكرتا الإسلامية الحكومية - Galih Ismail Abdul Rozaq Al Fadjri; Toto Suharto (Rayah Al-Islam, 2021)
ملخص البحث إن المواد التعليمية مهمة جدا فى عملية التعليم و التعلم. و لا بد أن تكون المواد التعليمية مطابقا بعملية التعليم. و يجرى تعليم اللغة العربية فى جامعة سوراكرتا الإسلامية عبر الانترنيت. فتحتاج المواد التعليمية على أساس أندرويد لتفعيل عملية التعليم و التعلم فيها. يستهدف هذا البحث لمعرفة الصورة العامة للمواد التعليمية لدرس خصوصي للغة العربية 2 جامعة سوراكرتا الإسلامية الحكومية و كيفية تطوير المواد التعليمية لدرس خصوصي للغة العربية 2 على أساس أندرويد و لمعرفة الجدوى من المواد المطور. هذا البحث يستخدم فيه طريقة البحث و التطوير. و أدوات جمع البيانات هي الملاحظة و المقابلة و الاستبيان. تحقيق المنتج المطوّر من الخبراء و الطلاب. و تقنية تحليل البيانات بالتحليل الوصفي و الكمّي. و نتيجة البحث هي: 1. استخدم الباحث فى تطوير المواد التعليمية على أساس أندرويد نموذج التطوير من بورغ وغال. و المنصة المستخدمة لتطوير المواد التعليمية هي منصة قادولار. 2. و النتيجة الأخيرة من المدقّقين من جوانب المادة و التعليم و العرض يحصل على المعدّل 3,616 فى الفئة "جيد جدا". و النتيجة الأخيرة من قبل طلاب من ناحية جوانب العرض يحصل على المعدّل 3,2 فى الفئة "جيد". استنادا إلى النتائج السابقة بمعنى المواد التعليمية المطوّرة ممكن الاستخدام فى تعليم اللغة العربية. Abstract Teaching materials are very important in the teaching and learning process. The educational materials must be in line with the teaching process. The Arabic language is taught at the Islamic University of Surakarta via the Internet. So the educational materials based on Android is needed to activate the teaching and learning process in it. This research aims to know the general picture of the educational materials for a private Arabic language lesson 2 at the State Islamic University of Surakarta and how to develop educational materials for an Arabic private lesson 2 on the basis of Android and to know the feasibility of the developed materials. This research uses the research and development method. The data collection tools are observation, interview and questionnaire. Achieving the product developed by experts and students. And the technique of data analysis by descriptive and quantitative analysis. The results of the research are: 1. In developing educational materials based on Android, the researcher used the development model from Borg and Gall. And the platform used to develop educational materials is the Kodular platform. 2. The final score of the auditors in terms of subject, education and presentation gets an average of 3,616 in the category “Very Good”. And the last score by students in terms of presentational aspects gets an average of 3,2 in the "good" category. Based on the previous results, meaning that the developed educational materials can be used in teaching Arabic.